DAMPAK KEPUASAN KERJA TERHADAP KINERJA PERAWAT SELAMA PANDEMI COVID-19 DI LOKASI REHABILITASI BNN DELI SERDANG - Yunita Syahputri Damanik; Viktor Edyward Marbun; Ripai Siregar (Jurnal Penelitian Kesmasy, 2020)
Nurses are the spearhead of whether or not the health services provided to patients are good because for 24 hours the nurse always interacts with the patient. The success of nursing services and services is largely determined by the performance of the nurses, so that an increase in the performance of nurses is necessary and must always be carried out through a standardized system so that the results are more optimal. One of the efforts to improve the performance or quality of health services, in this case nurses, needs job satisfaction. This study aims to determine the effect of job satisfaction on nurses during the COVID 19 pandemic at the BNN Deli Serdang Rehabilitation Workshop in 2020. This type of research is a quantitative study with an analytical observational research design designed in a cross sectional manner. The population of this study were 14 nursing staff both ASN and PPNPN who worked at the Deli Serdang Rehabilitation Center. Data collection was carried out using primary data and secondary data. The research instrument was a questionnaire sheet. The data were then processed and analyzed using the Spearman test and multiple linear regression. After doing the research, the results show that sig. = 0.001 for the salary variable, sig = 0.046 for the promotion variable, sig. = 0.036 for the monitoring variable, sig. = 0.008 for the peer-to-peer relationship variable and sig = 0.853 for the job variable itself. The conclusion is that there is an effect of salary, promotion, supervision and peer-to-peer relations on the performance of nurses, but there is no effect of the work itself on the performance of nurses. So it is suggested to the BNN Deli Serdang Rehabilitation Workshop to increase the amount of salary and especially in providing fairer incentives, because salary is job satisfaction that has the greatest influence on nurses in implementing nursing care.